On B * c-Convergence of Filters - Al - shabbani, Ali Kadhim; Al – Abdulla, Raad Aziz Hussain (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
In this paper we introduce and study types of convergence in topological spaces namely, convergence of filters by using the concept of open sets. Also, some properties of cluster points of filters has been studied.